ChemInform Abstract: Sono‐Transition‐Metal Catalysis of One‐Pot Three‐Step Synthesis of Glycosyl‐1, 2, 3‐triazoles. Issue 40 (12th September 2013) - Driowya, Mohsine; Bougrin, Khalid; Benhida, Rachid
Abstract An efficient and eco‐friendly three‐step one‐pot procedure for the synthesis of a new series of glycosyl triazoles is developed using ultrasonic activation and iron‐copper dual catalysis.